INTEGRATED MARKETING COMMUNICATION AND LOYALTY MODEL - Roli Martin (UNISSULA, 2017)
The rapid development of information technology and telecommunications companies to encourage dynamic can innovate and create high-tech products. One of emerging technology is currently the technology of fiber optic networks. Where using a fiber optic network so speed in accessing the internet could be faster and more stable. With some excess owned, fiber optic network also has some disadvantages. Some disadvantages include fiber optic network cables that easily break up and also the cost of expensive treatments. Because of this technology using a cable, then the terms of the program become obstacles for companies to be able to build the network on potential areas to be consumers or customers. With the limitations of the company engaged in is required to be able to market its products in order to make the network already built can be sold to the maximum. This research aims to analyze the influence of integrated marketing on customer loyalty and brand image as an intervening variable. This research was conducted in the city of Semarang with the population in this research is the whole industry customers telecommunication in Semarang city. Data obtained using a descriptive survey method that is explanatory by the number of respondents by as much as 90. Retrieval technique of sampling the sampling method using accidental. Results of the study indicate that Integrated Marketing Communication positive and significant effect against the Brand Image that implicates against loyalty. The results of this research also show going mediation by variable Brand Image so that the higher the Brand Image of a company they will make increasingly loyal customers. Loyalty or Loyalty can also be optimized through public relation activities and sales promotion are getting upgraded.Keywords : Integrated Marketing Communication, Brand Image, Loyalty